Absorption cross section of canonical acoustic holes - Crispino, Luís C. B.; Oliveira, Ednilton S.; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2007)
We compute numerically the absorption cross section of a canonical acoustic hole for sound waves with arbitrary frequencies. Our outputs are in full agreement with the expected low- and high-frequency limits. © 2007 The American Physical Society.